1982
DOI: 10.3133/ofr82526
|View full text |Cite
|
Sign up to set email alerts
|

Late Cenozoic stratigraphy and structure of the western margin of the central San Joaquin Valley, California

Abstract: Late Cenozoic Stratigraphy Late Cenozoic deposits in the west-central San Joaquin Valley and adjacent foothills of the Diablo Range consist mainly of unconsolidated, poorly-sorted to well-sorted gravel, sand, silt and clay derived primarily from the Diablo Range and secondarily from the Sierra Nevada. Sedimentary structures.* such as channeled contacts, laminated bedding, cross-stratification and clast-imbrication indicate that most of the deposits were transported and laid down by running water. These deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…This relationship can be demonstrated for deposits of late Modesto, early Modesto, and late Riverbank age, where non-glacial alluvium overlies glacial outwash with no evidence of a buried soil. This relationship is also observed by Lettis (1982), who demonstrated that non-glacial alluvium derived from the western San Joaquin Valley post-dates Sierra Nevada derived glacial outwash without evidence of a buried soil. These relationships indicate that an episode of nonglacial alluviation occurred during several glacial to interglacial transitions.…”
Section: Age Estimates For the Alluvial Sequence Of The Antelope Valleysupporting
confidence: 69%
“…This relationship can be demonstrated for deposits of late Modesto, early Modesto, and late Riverbank age, where non-glacial alluvium overlies glacial outwash with no evidence of a buried soil. This relationship is also observed by Lettis (1982), who demonstrated that non-glacial alluvium derived from the western San Joaquin Valley post-dates Sierra Nevada derived glacial outwash without evidence of a buried soil. These relationships indicate that an episode of nonglacial alluviation occurred during several glacial to interglacial transitions.…”
Section: Age Estimates For the Alluvial Sequence Of The Antelope Valleysupporting
confidence: 69%
“…Propagation of the sympathetic bulge from the Coast Ranges to the central Foothills area during the Quaternary provides a mechanism for the temporary partitioning off of the Great Valley, and the formation of the Corcoran Lake internal basin. The map distribution of Corcoran Lake based on abundant subsurface data from the 710-615 ka Corcoran E-clay (Frink and Kues, 1954;Lettis, 1982Lettis, , 1988 is shown in Figure 6, and its known subsurface distribution is shown in the structure sections in Figures 5 and 8. The northern limit of the lake parallels the broad culmination of the central Foothills swell, and the age of the lake corresponds in time to constraints presented earlier for growth of the Kern arch.…”
Section: Longitudinal Vertical Displacement Profi Les Along the Eastementioning
confidence: 99%
“…The release of sediment during these glaciations was responsible for at least five episodes of aggradation and progradation on stream-dominated alluvial fans along the eastern San Joaquin Valley, including the Kings River alluvial fan (Marchand 1977;Huntington 1980;Marchand and Allwardt 1981;Lettis 1982Lettis , 1988. Interglacial periods, similar to the present climate, left the upper alluvial fans exposed to pedogenic alteration and incision (Arkley 1962;Janda 1966;Shlemon 1971;Marchand 1977;Huntington 1980;Marchand and Allwardt 1981;Lettis 1982Lettis , 1988 (Huntington 1980;Arroues and Anderson 1986). The gray borders show the outline of maps shown in Figure 3.…”
Section: Study Areamentioning
confidence: 99%